Possessing Endowment - Yedi Purwanto; Hari Utomo; Rasyida Noor (Badan Wakaf Indonesia, 2017)
Possessing endowment refers to an association that cope the endowment properties from the endower in order to be managed and developed based on its intentions (UU no. 41 year 2004 article 1 section 4). According to Imam Syafi’i, possessing endowment can be comprised by wakif, or mauquf ‘alaih, or hakim. Dissimilarity with the constraints in the government regulations Number 28 Year 1977, possessing endowment should be managed by individuals or institutions in contrast with the constraints that are mentioned by Imam Syafi’i. Evenly, UU no. 41 Year 2004 article 9 has mentioned that possessing endowment may include: a. individuals, b. organizations, c. institutions. The main notions discussed in this study are: first, the concept of Imam Syafi’I, government regulation no. 28 Year 1977, and UU no. 41 Year 2004 about The Endowment of Land Properties; second, the position of possessing endowment according to Imam Syafi’i PP no. 28 Year 1977 about The Endowment of Land Properties, and UU no. 41 Year 2004. In addition, the aims of this study are: First, getting a description about the concepts delivered by Imam Syafi’i, government regulation no. 28 Year 1977, and UU no. 41 Year 2004 about The Endowment of Land Properties; Second, gaining a description about the position of possessing endowment according to Imam Syafi’I, PP no.29 Year 1977, and UU no. 41 Year 2004; Third, gaining a description about the influence of Imam Syafi’i perspectives in government regulation no. 28 Year 1977 and UU no. 41 Year 2004 about The Endowment of Land Properties, especially about the position of possessing endowment. This study is started by literature review of Imam Syafi’i works that relate to endowment appraisal and a review of government regulation no. 28 Year 1977 and UU no. 41 Year 2004 about the practice of endowment in Indonesia. The conclusion of this study gives an affecting description from Imam Syafi’i perspectives towards PP no. 28 Year 1977 and UU no.41 Year 2004 about the practice of endowment in Indonesia. In addition, the majority of Indonesian Muslims is enthusiastically involved in applying the concept of Imam Syafi’i in relation to the notion about possessing endowment in its practices. Keywords: Endowment, Possessing, Government Constitutions